A Study of Ideas in Ahmad Malada's Novel (Zakirah-i Ba) - غریب, آ.م.د. له‌نجه‌ عبدالرحمن غریب (Sulaimani Journal for Humanities, 2025)
Ahmadi Mullah's Zakiray Ba is a different novel from the Kurdish novel world, because it is not based on an ordinary novel, but on the narrative of the novelist's own childhood memories, ie Ahmadi Mullah's memories instead of his contemporaries He has mixed these memories with his creative imagination and put them within the framework of the artistic form of the novel genre. As he wrote on the cover of his book, instead of writing memoirs, Ahmadi Mullah has tried to tell them He should change the memories of his childhood and adolescence to narrate in the form of a novel genre, not keeping them in the ordinary cover of memory and hanging them in artistic narrative From the beginning, what he realizes is that what he is reading is a completely artistic novel. From this perspective, this study shows how to tell this memory in the form of a novel by focusing on the genres that make up both types of literature, such as characters, events, places, times and descriptions with examples taken from the novel.
Keywords: Narrative; Memoir; Novel; Event; Place